ADAPTASI SOSIO-EKOLOGI BUDIDAYA RUMPUT LAUT (EUCHEUMA COTTONII) PADA MASYARAKAT PESISIR DI KELURAHAN LAMALAKA, KECAMATAN BANTAENG, KABUPATEN BANTAENG - Farhanah Wahyu; Andi Adri Arief; Djumran Yusuf (Universitas Muhammadiyah Makassar, 2016)
This study aims to determine the state of socio-ecological adaptation of coastal communities to the development of seaweed cultivation, and the dynamics of technostructure of coastal communities in the development of seaweed farming in Sub Lamalaka, District Bantaeng. The usefulness of this research is as information for the government to educate coastal communities in environmental preservation seaweed farming so that those resources can be used sustainably. This research was conducted in March and April 2010 in the village of Lamalaka, District Bantaeng, Bantaeng. This location was chosen intentionally (purposive) in consideration that the area is an area of development of the cultivation of seaweed (E. Cottonii) at the same seaweed production areas in South Sulawesi. The method used is the snowball sampling method with the number of informants as many as 23 people. The results showed that the adaptation of the socio-ecology of coastal communities in Sub Lamalaka occurs through the relationship of social interaction between the members of coastal communities which are then adapted to the conditions of suitability to the development of seaweed farming sustainable and in the form of the dynamics of techno structures that are in a transitional phase between the use of irrational becomes rational technology.